Transformation of the Profane Meaning of the Cirebon Mask: a Creative Industry - Hadiyatno; Wiwin Purwinarti (Tsaqofah, 2023)
This article aims to examine and analyze the transformation of the profane meaning of the Cirebon mask in the creative industry. The mask transformation has significantly changed the economically supporting community, while for the government, the changes have provided foreign exchange for the country. The meaning of profane masks in the creative industry has made a positive trend for artisans; this is in line with changes in the social structure of Cirebon society and globally. Change has made its capital in the practice of cultural products by artisans. But from another perspective, the issue of cultural products in the creative economy concerns the emergence of capitalist practices and their strengths, especially by some artisans who remain loyal to the original value of masks. Departing from this point gave rise to internal turmoil and conflict in the Cirebon mask-supporting community. A paradox, the change issue is very complex, complicated, and full of contradictions. On the other hand, the current existence of masks can indirectly reinforce the sovereign integrity of masks in cultural dynamics. The writing of this article uses a qualitative method to be able to describe and analyze mask changes. The practice of transforming the meaning of masks is divided into three parts, Cirebon Mask, the transformation of profane meaning, and creative industries.